Cross Laminated Timber (CLT) Beams Loaded in Plane: Testing Stiffness and Shear Strength - Boggian, Francesco; Andreolli, Mauro; Tomasi, Roberto (Frontiers in Built Environment, 2019)
Cross Laminated Timber (CLT) is a relatively new timber product used in constructions that gained lots of popularity over the last decade. The product itself is constituted by multiple glued layers of juxtaposed boards, usually arranged in an opposite direction between one layer and the adjacent ones. This particular structure brings several benefits, i.e. the possibility to use the same product both for walls and slabs, since it can bear in plane and out of plane loads. However, the mechanical behavior differs from usual timber products, and research is still ongoing to achieve common agreement on standard procedures for testing and theories for evaluating stresses for safety verifications. This paper proposes to investigate the behavior of CLT beams loaded in plane by testing several specimen with a four point bending test setup according to the EN 408 procedure \cite{EN408}. The main goal is to analyze the shear behavior of these beams hence the particular geometry is specifically chosen to obtain in plane shear failure. First the matter is analyzed by a literature review to study the existing theories for the calculation of in plan shear stresses in CLT elements. Then the experimental campaign is reported, the first part regarding elastic range test for Modulus of Elasticity measurement and the second main part regarding the failure tests to investigate shear behavior with regard to different mechanisms. Last conclusions are made and results are compared with other existing tests and proposed values in literature.